POLA PEMUKIMAN KAMPUNG ADAT ANAKALANG: KEBERLANJUTAN BUDAYA MEGALITIK DI SUMBA TENGAH - Retno Handini (KALPATARU, 2019)
AbstractThis research aims to determine how the settlement pattern of Anakalang community in Central Sumba which are supporters of the megalithic tradition. This research also aims to determine the extent of sustainability of megalithic culture in the Anakalang region. The research methods carried out were participation observation, in-depth interviews and literature studies. Through the participatory observation method, the author is easier to know and understand the interconnectedness of the cultural elements of the Sumba community, especially concerning the place of residence. In-depth interview techniques were carried out on the informants. The results of the study show that the pattern of occupancy of traditional villages in Anakalang is almost entirely linear with houses facing each other, in the middle part of the village is a field (talora) where there are stone graves and traditional rituals are performed. Although many old traditional villages were abandoned and they established villages in new places, the strong kinship made the Anakalang community always return to their villages if there were traditional ritual events. As a settlement that has the characteristics of a megalithic tradition, traditional houses in Anakalang are almost certainly always associated with stone graves and menhirs. The establishment of stone tombs and traditional rituals are united in the daily lives of the Anakalang community, with a background of religious conceptions that are seen as ancestral heritage that must be held firmly. The variety of megalithic cultures in Anakalang has through the time period in a theoretical way, and continues to this day as a tradition. Keywords: Residential pattern, megalithic, Anakalang, Sumba Penelitian ini bertujuan untuk mengetahui bagaimana pola pemukiman masyarakat Anakalang di Sumba Tengah  yang merupakan pendukung tradisi megalitik. Penelitian ini juga bertujuan untuk mengetahui sejauh mana keberlanjutan budaya megalitik di wilayah Anakalang.   Metode penelitian yang dilakukan adalah observasi partisipasi, wawancara mendalam dan studi pustaka. Melalui metode observasi partisipasi,  penulis lebih mudah untuk mengetahui dan memahami keterkaitan unsur-unsur budaya masyarakat Sumba terutama menyangkut tempat tinggal. Teknik wawancara mendalam dilakukan terhadap para informan. Hasil penelitian menunjukkan bahwa pola pemukiman kampung adat di Anakalang hampir seluruhnya  berbentuk linier dengan rumah yang saling berhadapan, di bagian tengah kampung merupakan lapangan (talora) tempat kubur-kubur batu dan tempat melakukan ritual adat. Meski banyak kampung adat lama ditinggalkan dan mendirikan kampung di tempat baru   namun kuatnya kekerabatan membuat masyarakat Anakalang  selalu kembali ke kampung asal jika ada acara ritual adat. Sebagai pemukiman yang memiliki ciri tradisi megalitik, rumah adat di Anakalang hampir pasti selalu berasosiasi dengan kubur-kubur batu dan menhir.  Pendirian kubur batu dan ritual adat menyatu dalam keseharian masyarakat Anakalang, dengan latar belakang konsepsi religi yang dipandang sebagai warisan nenek moyang yang harus dipegang teguh. Ragam budaya megalitik di Anakalang telah menembus batas periode waktu secara teoritis, dan berlangsung hingga kini sebagai sebuah tradisi. Kata kunci : Pola hunian, megalitik, Anakalang, Sumba